An Orthographic Effect in Phoneme Processing, and Its Limitations - Cutler, Anne; Davis, Chris (Frontiers in Psychology, 2012)
To examine whether lexically stored knowledge about spelling influences phoneme evaluation, we conducted three experiments with a low-level phonetic judgement task: phoneme goodness rating. In each experiment, listeners heard phonetic tokens varying along a continuum centred on /s/, occurring finally in isolated word or nonword tokens. An effect of spelling appeared in Experiment 1: Native English speakers’ goodness ratings for the best /s/ tokens were significantly higher in words spelled with S (e.g., bless) than in words spelled with C (e.g., voice). No such difference appeared when nonnative speakers rated the same materials in Experiment 2, indicating that the difference could not be due to acoustic characteristics of the S- versus C-words. In Experiment 3, nonwords with lexical neighbours consistently spelled with S (e.g., pless) versus with C (e.g., floice) failed to elicit orthographic neighbourhood effects; no significant difference appeared in native English speakers’ ratings for the S-consistent versus the C-consistent sets. Obligatory influence of lexical knowledge on phonemic processing would have predicted such neighbourhood effects; the findings are thus better accommodated by models in which phonemic decisions draw strategically upon lexical information.